From Resistance to Resilience: A Feminist Approach in the Novels of Shashi Deshpande - Aayushi Sharma, Dr. Rakesh Gupta, Lalit Kishore Sharma (International Journal of Modern Agriculture, 2021)
Patriarchal society makes women suffer mental traumas right from their birth. While few women endure the odds, others end up in losing their lives. Women who experience trauma are either mentally ill or neglect their traditional beliefs. This paper aims to study the resistance and resilience of women in select novels of Shashi Deshpande. Shashi Deshpande is one of the most prolific contemporary Indian Woman Writer. Her writing highlights the issues faced by women in the patriarchal society. This paper can be divided into three parts. The first section is intended to illustrate women's resilience and restrain in the face of a commonly assumed asymmetrical stereotypical patriarchal structure, as well as an outline of theorists and writers whose concepts and ideas aided women's resilience regardless of unfair structures. The second section gives a brief overview of Shashi Deshpande and her place in Indian English literature. The third section features the themes of resistance, resilience, and women empowerment in her novels. Three of Shashi Deshpande's novels were considered for this study specifically ‘The Dark Holds No Terrors’, ‘Roots and Shadows’, and ‘That Long Silence’. The women characters of her novels are the victims of patriarchy and are coiled in the ropes of traditional beliefs of the society. In the world of male dominance, they face struggles, injustice and are profoundly distressed physically and mentally. But the power and inner strength of these women to bounce back and regain their original state is what the paper aims to explore.